Pika Population Density Is Associated with the Composition and Diversity of Gut Microbiota - Li, Huan; Qu, Jiapeng; Li, Tongtong; Li, Jiabao; Lin, Qiang; Li, Xiangzhen (Frontiers in Microbiology, 2016)
Host population density is positively associated with the strength of social interactions or the frequency of physical contacts, and thus potentially influences microbial transmission among individuals. However, the relationship between host density and gut microbiota remains unknown. Here, we characterized the gut microbiota of plateau pikas (Ochotona curzoniae) in wild experimental fields with different host population densities. The abundance of some gut microbes significantly correlated with host density, such as Ruminococcaceae, Lachnospiraceae and Staphylococcaceae. Intriguingly, host density was positively correlated with alpha diversity (Shannon diversity and observed species) of gut microbial communities. The inter-individual gut microbiota within high-density groups were more similar to each other than those of low-density groups. Host density significantly explained the variations in the gut microbiota, even after controlling sex, weight, diet and geographical locations. Based on the PICRUSt metagenome prediction, positive correlations were observed between host density and the relative abundances of 12 gene functions involved in cellular processes, environmental information processing and metabolism. These results indicate the importance of host density as a factor in shaping gut microbial composition and diversity in plateau pikas, and may further help us understand the social transmission of gut microbiota.